One-Step Hydrothermal Synthesis of Nanostructured MgBi2O6/TiO2 Composites for Enhanced Hydrogen Production - Feng Xu; Chaohao Hu; Di Zhu; Dianhui Wang; Yan Zhong; Chengying Tang; Huaiying Zhou (Nanomaterials, 2022)
A highly efficient MgBi2O6 (MBO)/TiO2 heterostructured photocatalyst for the evolution of H2 was successfully prepared using a one-step hydrothermal method. The phase structure, microstructure and optical properties of the MBO/TiO2 composites were investigated by various experimental techniques. A series of H2 production experiments were performed under visible light. The measured results indicated that the nanostructured MBO/TiO2 composite, with a stoichiometric molar ratio of MBO:TiO2 = 0.2%, displayed the best H2 production rate of 3413 μmol h−1 g−1. The excellent photocatalytic performance of the obtained composite material was due to the heterojunction formed between MBO and TiO2, which reduced the charge transfer resistance and accelerated the separation efficiency of the photogenerated electron–hole pairs. The reaction mechanism was also discussed in detail.